Fungal population on seeds of Arachis hypogea L. - Editor, Jogdand S.K.* and Talekar S.M. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">The seed of four groundnut varieties viz. Gujrat, Western, Ghungroo and Local were collected from different market places of Beed, (M.S.) and seed mycoflora was isolated by standard blotter paper method and agar plate method. In all the four varieties seeds exhibited maximum number of fungi with higher percentage of incidence. Aspergillus flavus. A. niger, Fusarium oxysporum, Macrophomina phaseolina Penicillium sp. were found predominant. Higher numbers of fungi were isolated on agar plate method used as compared to standard blotter paper method. Surface sterilization with HgCl2 reduces the incidence of Aspergillus flavus and Aspergillus niger. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">--- <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';"> P.G. Department of Botany, Mrs.K.S.K. College Beed- 431122 (M.S.), India --- <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';"> Please Cite This Article As: S.K. Jogdand and S.M. Talekar. 2010. Fungal population on seeds of Arachis hypogea L. J. Ecobiotechnol. 2(6):11-13.